A taxonomic revision of Aloe sect. Purpurascentes (Asphodelaceae subfam. Alooideae) - Klopper, Ronell R.; Grace, Olwen M.; Klopper, Arrie W.; Smith, Gideon F.; Wyk, Abraham E. Van (Phytotaxa, 2023)
Aloe sect. Purpurascentes, or the speckled aloes (not to be confused with the maculate aloes, which are members of A. sect. Pictae), occurs in southern and western South Africa and southern Namibia. This section is here revised using macro-morphology, seed morphology, palynology, chemistry, and molecular evidence. Seed morphology, palynology, chemistry, and to a greater extent molecular markers, are shown to be inconclusive for demarcation at species level in A. sect. Purpurascentes. Nonetheless, evidence from these sources does provide support for the general coherence of the group. Although some species can be clearly differentiated from most other members of A. sect. Purpurascentes, the results are not consistent among the different character sets investigated. No changes are thus proposed here in terms of the placement of taxa within the section. Two species suspected to be members of the section under study (A. pictifolia and A. chlorantha), although being chemically related, do not cluster with the rest of the members of A. sect. Purpurascentes in the morphological analysis, and evidence on the sectional placement of these taxa from molecular analyses is inconclusive. Hence, these two aloes are here excluded from A. sect. Purpurascentes. The most useful evidence to distinguish among taxa in A. sect. Purpurascentes were those from comparative morphology. In this revision five species are retained: A. framesii, A. gariepensis, A. khamiesensis, A. microstigma, and A. succotrina. The following taxonomic changes are proposed: A. knersvlakensis becomes a subspecies of A. khamiesensis; aberrant populations of the latter species from the Hantam region are described as A. khamiesensis subsp. hantamensis; A. juttae is reinstated at subspecific level under A. microstigma; A. amoena is reinstated at subspecific level under A. framesii, and a third subspecies, A. framesii subsp. maraisii, is described for the southern populations of this aloe. Lectotypes are designated for five names and epitypes for three names. The notion that DNA barcodes should not be seen as a replacement technique for comprehensive taxonomic analysis is clearly illustrated in this revision of A. sect. Purpurascentes. Since traditional barcodes are insufficient to distinguish samples at species level, alpha taxonomic techniques are essential to delimit species in this group of aloes, and likely for all other aloes.